2014
DOI: 10.5897/ajar2013.7291
|View full text |Cite
|
Sign up to set email alerts
|

Soil fertility changes and their effects on ginger (Zingiber officinale Rosc.) yield response in an ultisol under different pigeon pea hedgerow alley management in South Eastern Nigeria

Abstract: Short term changes that occur in soil properties of an ultisol under different pigeon pea hedgerow alley populations and inter-hedgerow alley spacing and the effect of such changes on ginger rhizome yield response were evaluated in a two-year (2010 and 2011) field study in South Eastern Nigeria. Treatments comprised pigeon pea hedgerow alley populations of 20,000, 33, 333 and 66, 667 plants/ha in factorial combinations with three inter-hedgerow alley width spacing of 1, 2 and 3 m in a randomized complete block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Ginger is usually intercropped in coconut, areca nut, coffee and orange plantations in Kerala and Karnataka [ 30 ]. Changes in soil fertility for improved growth of ginger under different quantities of pigeon pea hedgerow alley management produced a significant increase in ginger yield [ 33 ]. Another important technique is propagation by using internodal cuttings [ 34 ].…”
Section: Genus Zingiber Plant Cultivationmentioning
confidence: 99%
“…Ginger is usually intercropped in coconut, areca nut, coffee and orange plantations in Kerala and Karnataka [ 30 ]. Changes in soil fertility for improved growth of ginger under different quantities of pigeon pea hedgerow alley management produced a significant increase in ginger yield [ 33 ]. Another important technique is propagation by using internodal cuttings [ 34 ].…”
Section: Genus Zingiber Plant Cultivationmentioning
confidence: 99%
“…Accurately 100 g of sample was weighed, and it was spread on a white tile uniformly and inspected visually using a lens. The foreign organic matter was separated manually [17]. After complete separation, the collected foreign organic matter was weighed and the percentage in w/w present in the sample was calculated by using the following formula.…”
Section: Determination Of Foreign Organic Mattermentioning
confidence: 99%
“…Ginger is generally cultivated as intercropping or planted under the tree in agroforestry systems, ranging from lowland to upland. The study in South Eastern Nigeria by Nwaogu (2014) reported that planting ginger in-between pigeon pea hedgerow alleys improved soil fertility (i.e exchangeable Ca, Mg, K, base saturation, soil organic C, and available P). While planting ginger under the shade trees in agroforestry system ginger can grow well and tolerate up to 45 to 55% shading (Pandey, Shukla, Saxena, Khan, & Kumar, 2018).…”
Section: Introductionmentioning
confidence: 99%